AKHṬᾹ’ NASKHI KITᾹBATIL ISMI MIN AL-LUGAH AL-INDŪNĪSIYYAH ILᾹ AL-LUGAH AL-‘ARABIYYAH LI-ṬOLABATI JᾹMI’ATI MAULᾹNA MᾹLIK IBRᾹHIM MALANG - Kirom, Makhi Ulil; Maghfur, Taa’ib (Annual International Conferences on Language, Literature, and Media, 2023)
The name becomes a special identity that is owned by each individual. Therefore, choosing a name is very important for someone, because the name will be a marker as well as the hope of the giver and owner of the name. On the other hand, the social environment where a person is born, the scientific background of parents, and the culture that is developing when a person is born also has a strong influence on the choice of a name. In some conditions a person needs to make adjustments to their name for certain purposes, such as transliterating it into another language such as Arabic. This process turned out to cause several problems for the owner of the name. This research was conducted to find out the main causes of transliteration errors. The objects of this study were students of the Faculty of Humanities, State Islamic University of Maulana Malik Ibrahim Malang for the academic year 2022/2023 who registered for a certificate in the Arabic Language Lecture Special Program. In this study, classification of these names was carried out based on the structure of the name formation to find the background causes of student errors when transliterating these names using orthographic studies. Based on this study, it was found that the scientific background of students greatly influences the validity of transliterating names from Indonesian to Arabic. Besides that, the type of structure that makes up the name also has a significant influence on the level of ease or difficulty of writing the name.